Screening for thyroid disease in a primary care unit with a thyroid stimulating hormone assay with a low detection limit. Issue 6663 (17th December 1988) - Eggertsen, R.; Petersen, K.; Lundberg, P. A.; Nyström, E.; Lindstedt, G.
Abstract : In a study at a primary care centre in a predominantly rural area of Sweden the records of all patients with established thyroid disease were scrutinised and 2000 consecutive adult patients screened with an immunoenzymometric thyroid stimulating hormone assay. The aims of the study were fourfold: firstly, to assess the total burden of thyroid disease in primary care centres in Sweden; secondly, to assess the efficacy of clinical diagnosis of the disease in unselected populations of patients; thirdly, to assess the efficacy of clinical evaluation of treatment with thyroxine; and, lastly, to see whether a single analysis of the serum thyroid stimulating hormone concentration by recent methods would be enough to identify an abnormality of thyroid function. Of the roughly 17, 400 adults in the study community, 111 women and 10 men were being treated for thyroid disease. Screening detected 68 patients (3.5%) not receiving thyroxine who had a serum thyroid stimulating hormone concentration of 0.20 mU/l or less, all of whom were followed up clinically. Fifty of these patients were also studied biochemically during follow up. Only nine of the 68 patients had thyroid disease (three with thyrotoxicosis requiring treatment), no evidence of the disease being found in the remainder. Sixteen patients had spontaneous hypothyroidism requiring treatment, and neither these nor three patients with thyrotoxicosis had been detected at the preceding clinical examination. Of 35 patients in whom thyroid disease was suspected clinically at screening, none had laboratory evidence of thyroid dysfunction. In this series 1.3% of all women in the study community (2.6% of all 50-59 year olds) and 0.1% of the men were being treated for thyroid disease at the primary care centre, roughly 1.0% of adults subjected to screening were found to have thyroid disease requiring treatment, and most patients with a thyroid stimulating hormone concentration of 0.20 mU/l or less did not have thyroid dysfunction. It is concluded that measuring the basal serum thyroid stimulating hormone concentration by present methods is insufficient for the biochemical assessment of thyroid dysfunction in unselected populations.